1)a)ta có :(a+b)[(a-b)2+ab]=(a+b)(a2-2ab+b2+ab)
=(a+b)(a2-ab+b2)
=a3+b3
b) ta có :(a+b+c)3=a3+b3+c3+3a2b+3a2c+3b2c+3b2a+3c2a+3c2b+6abc
(a+b+c)3=a3+b3+c3+(3a2b+3a2b+3abc)+(3b2c+3b2a+3abc)+(3c2a+3c2b+3abc)-3abc
(a+b+c)3=a3+b3+c3+3ab(a+b+c)+3bc(a+b+c)+3ac(a+b+c)-3abc
(a+b+c)3=a3+b3+c3+3(a+b+c)(ab+bc+ac)-3abc
thay a+b+c=0 ta được
03=a3+b3+c3+3.0(ab+bc+ac)-3abc
0=a3+b3+c3-3abc
=>a3+b3+c3=3abc
a+b+c=0
=>(a+b+c)3=0
=>a3+b3+c3+3a2b+3ab2+3b2c+3bc2+3a2c+3ac2+6abc=0
=>a3+b3+c3+(3a2b+3ab2+3abc)+(3b2c+3bc2+3abc)+(3a2c+3ac2+3abc)-3abc=0
=>a3+b3+c3+3ab(a+b+c)+3bc(a+b+c)+3ac(a+b+c)=3abc
Do a+b+c=0
=>a3+b3+c3=3abc(ĐPCM)